2020
DOI: 10.1037/ccp0000468
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in response to metacognitive training in people with first-episode psychosis.

Abstract: Introduction: The study aimed to assess gender differences in the efficacy of metacognitive training (MCT) in people with first-episode psychosis in terms of symptoms and cognitive insight as a primary outcome and other metacognitive and social cognition measures as a secondary outcome. Method: A multicenter, controlled, randomized clinical trial was performed including 122 patients with first-episode psychosis. A total of 8 weekly group sessions of MCT or a psychoeducational intervention were performed. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 61 publications
0
18
1
Order By: Relevance
“…and metacognitive training (combining psychoeducational components and cognitive behavioural therapies) seems to be more effective in women. [30,31] We can only speculate if the women in our group were more perceptive to subjective improvements, or were more susceptible to delivering supposedly expected or positive results. A large interview-based survey found that women who used CAM were more likely to report positive outcomes and greater benefit compared to male CAM users.…”
Section: Plos Onementioning
confidence: 88%
“…and metacognitive training (combining psychoeducational components and cognitive behavioural therapies) seems to be more effective in women. [30,31] We can only speculate if the women in our group were more perceptive to subjective improvements, or were more susceptible to delivering supposedly expected or positive results. A large interview-based survey found that women who used CAM were more likely to report positive outcomes and greater benefit compared to male CAM users.…”
Section: Plos Onementioning
confidence: 88%
“…Although many studies do not reveal gender differences in social cognition in FEP, some authors have reported that men and women with FEP show distinct outcomes in interventions targeting social cognition. For instance, Salas-Sender et al [27] showed a reduction in the personalizing bias scores in women with FEP, but not in men, after metacognitive training. A possible explanation for this might be that mediating factors exist between gender and social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…No other participant or treatment characteristic emerged as a moderator between MCT and any other proximal or distal outcome. Prior evidence suggests that women may improve more in general symptoms compared with men after MCT ; however, no sex-specific benefits were observed following meta-analysis.…”
Section: Discussionmentioning
confidence: 99%